2008
DOI: 10.5089/9781451869217.001
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Growth Sustained?

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.We identify structural breaks in economic growth in 140 countries and use these to define "growth spells:" periods of high growth preceded by an upbreak and ending either with a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This pattern of robust growth accompanied by little decline in inequality in LIDCs is a concern. On average, economies with lower income inequality experience longer spells of sustained growth (Ostry, Berg, and Zettelmeyer, 2012), as well as higher growth rates (Dabla-Norris and others, 2015). Widening inequality can also weaken support for growth-enhancing reforms and may spur governments to adopt populist policies, threatening economic and political stability (Rodrik, 1999).…”
mentioning
confidence: 99%
“…This pattern of robust growth accompanied by little decline in inequality in LIDCs is a concern. On average, economies with lower income inequality experience longer spells of sustained growth (Ostry, Berg, and Zettelmeyer, 2012), as well as higher growth rates (Dabla-Norris and others, 2015). Widening inequality can also weaken support for growth-enhancing reforms and may spur governments to adopt populist policies, threatening economic and political stability (Rodrik, 1999).…”
mentioning
confidence: 99%
“…Data has also revealed that the share of the national income associated with labor has declined in nearly all CIS countries when productivity has been rising much faster than the real wages across these countries (Dabla-Norris, E. et al, 2015). In the context of the labor share, it has been documented that the highest earners have been getting increasingly large portions while their counterparts at the bottom have experienced declined shares (Ostry, J. & Berg, A., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Jerzmanowski (2006) following Markov switching logic for 89 countries in 32 years found switching among growth regimes (miracle growth, stable growth, stagnation, and crisis) based on the severity of terms of trade shocks, which is mainly determined by the quality of institutions. Berg Ostry and Zettelmeyer (2006) analysed so-called 'growth spells' as the period of acceleration and deceleration in growth by observing 140 countries through panel data analysis and found that external shocks, such as in terms of trade are negatively associated with growth spells, but their overall importance is small. Empirical facts suggest that it is crucial to monitor the process of terms of trade, i.e., its process changes since terms of trade can have low-and highfrequency fluctuations and in that manner shift in a regime.…”
Section: Literature Reviewmentioning
confidence: 99%